Lead monitoring and control in tobacco products and E-cigarettes by molecular fluorescence - Talio, María Carolina (2019)
A new methodology for lead traces determination has been developed based on the quenching effect on fluorescent emission of the complex formed by the metal with 8‑hydroxyquinoline and o-phenanthroline at λ em = 365 nm (λ exc = 250 nm). Experimental variables that influence on fluorimetric sensitivity were optimized using uni-variation assays. The calibration graph using zero th order regression was linear from 1.21 μg L −1 to 518 μg L −1 , with correlation coefficient better than 0.999. Under the optimal conditions, the limits of detection and quantification were of 0.42 μg L −1 and 1.21 μg L −1 respectively. The proposed method showed good sensitivity, adequate selectivity with good tolerance to foreign ions, and was applied to the determination of trace amounts of lead in leachate of tobacco products and refill solutions for e-cigarettes with satisfactory results. The trueness of the recommended procedure was assessed trough parallel analysis of the samples by ICP-MS. The proposed method represents an innovative application of luminescence to metal analysis comparable in sensitivity and accuracy to atomic spectroscopies.